Pengaruh Pengalaman Kerja, Kompensasi,Motivasi Dan Training Terhadap Kinerja Pegawai PLN Cabang Solo - Wijayanto, Arie; , Sri Murwanti SE., MM (2017)
This study aimed to determine the effect of work experience, compensation, motivation, and training on the performance of branch office employees PLN Solo. The sample used in this study were 70 respondents. The analysis tool with the help of SPSS software and using validity, reliability test, classic assumption test and multiple linear regression analysis. The findings indicate that work experience, compensation, motivation, and training partially and simultaneously significant effect on employee performance. At determinant coefficient illustrates that porsentase donations influence work experience, compensation, motivation, and training together to employee performance amounted to 36.1% and still have the effect of other variables of 63.9%.